La Copa Leisure Centre / Muhammad Khairul Anwar ... [et.al] - Ibrahim, Muhammad Khairul Anwar; Mokhtar, Mohd Azizi; Suliman, Mohd Azizi Arifin; Zulkafli, Norlizana Fazlia; Abdullah, Husaifah; Ismail, Nurizati (Faculty of Architecture, Planning and Surveying, 2005)
La Copa Leisure Centre is established as a result of the survey and research made by the La Copa Enterprise to add another facility for the people in Shah Alam. The plan made for this business is because of the increasing potential and demand of futsal. Besides that, we also provide a cafe that serves western foods and drinks. That is a which is situated at No.9/8 Jin Plumbum, Section 7,41010 Shah Alam, Selangor Darul Ehsan. The objective of building up the cafe at the La Copa Leisure Center is to create a place where the customers especially the teenagers can hang out and spend their free time in a positive and healthy way. Teenagers can make the cafe as a medium to socialize and spend time with their friends. Plus, they can even watch futsal game from there. The La Copa Leisure Center will start to operate fully on January 2006. The factor that had influenced the establishment of the business is because of the demand of the futsal game that is increasing and also the need of creating a new place for the teenagers to hang out at.